The impact on quality of life on families of children on an elimination diet for Non-immunoglobulin E mediated gastrointestinal food allergies - Meyer, Rosan (World Allergy Organ J, 2017)
BACKGROUND: The impact on health related quality of life (HRQL) has been well studied in children with Immunoglobulin E (IgE)-mediated food allergy. However limited data exists on related quality of life (QOL) of families who have a child suffering from food protein induced non-IgE mediated gastrointestinal allergies. We aimed to establish the QOL of families with children at the beginning of following an elimination diet for non-IgE mediated gastrointestinal food allergies. METHODS: A prospective, observational study was performed. Parents of children aged 4 weeks–16 years who improved after 4–8 weeks of following an elimination diet for suspected non-IgE mediated allergies were included. The Family Impact Module (FIM) of the Pediatric Quality of Life (PedsQL™) was used and we compared our data to two historical cohorts: one with sickle cell disease and another with intestinal failure. RESULTS: One hundred and twenty three children with a median age of 20 months were included (84 boys). The total FIM Score was 57.43 (SD 22.27) and particularly low for daily activities and worry. Factors that impacted significantly included age (p < 0.0001), number of foods excluded (p = 0.008), symptom severity (p = 0.041) and chronic nasal congestion (p = 0.012). Children with non-IgE mediated food allergies had worse scores in all domains (p < 0.0001) compared to sickle cell disease and worse physical (p = 0.04), emotional (p = 0.04) and worry (p = 0.01) domains compared to intestinal failure. CONCLUSIONS: This study found that parent QOL and family functioning was worse in those families who had a child on an elimination diet for non-IgE mediated allergies compared to those with sickle cell disease and intestinal failure, highlighting the impact this disease has on families.